West Bank and Gaza : Report to the Ad Hoc Liaison Committee. (IMF Staff Country Reports; Country Report ;, 2022)
This IMF report to the AHLC is the first since September 2018. Following limited engagement over the past three years, policy discussions have intensified in recent months. These discussions have focused mainly on establishing a medium term macro-fiscal framework, including the broad outlines of a reform scenario.